Enhancing Business Acumen in Rural Entrepreneurs: A Community-Based Training and Mentorship Program - Aripin (Jurnal Abdimas Peradaban, 2023)
Rural entrepreneurs face various constraints and challenges, such as limited access to capital, technology, and markets, which hinder the development of their businesses. The need for training and mentoring programs that can improve their skills and knowledge is urgent. Community-based programs that involve entrepreneurs and local communities in planning and implementation can be an effective solution. This study aims to develop and evaluate a community-based training and mentoring program for rural entrepreneurs. This study was conducted using a qualitative approach, using data from various relevant sources, such as research results and previous studies. The collected data were then processed to find significant results. The conclusion of this study shows that a participatory approach in training and mentoring programs is essential to ensure the relevance and effectiveness of the program. The curriculum that includes business management, marketing, and information technology has been proven to meet the specific needs of rural entrepreneurs. The role of competent facilitators and active community participation support the successful implementation of the program. Continuous evaluation using surveys, interviews, and observations ensures the program can be continuously improved and adjusted. The program has positive long-term impacts, including skills improvement, local economic development, and new job creation, as well as ensuring sustainability through partnerships and sustainable business models.